Mouse Models in Arrhythmogenic Right Ventricular Cardiomyopathy - Lodder, Elisabeth M.; Rizzo, Stefania (Frontiers in Physiology, 2012)
Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a heart muscle disorder characterized by fibro-fatty replacement of cardiomyocytes. The cardinal manifestations are arrhythmias, sudden cardiac death, and seldom heart failure. Mutations in genes encoding desmosomal proteins and their interaction partners have been implicated in the pathogenesis of ARVC and it is now widely accepted that ARVC is a disease caused by abnormal cell–cell adhesion. The mechanism(s) by which mutations in desmosomal proteins lead to fibro-fatty replacement remains to be fully elucidated. To this aim over the last 10 years different transgenic and targeted mouse models have been developed, these models and what they have taught us will be discussed in this review.